The anti‐inflammatory effects of PGE2 on human lung macrophages are mediated by the EP4 receptor. (6th September 2016) - Gill, Sharonjit K; Yao, Yiwen; Kay, Linda J; Bewley, Martin A; Marriott, Helen M; Peachell, Peter T
Abstract : Background and Purpose: PGE2 inhibits cytokine generation from human lung macrophages. However, the EP receptor that mediates this beneficial anti‐inflammatory effect of PGE2 has not been defined. The aim of this study was to identify the EP receptor by which PGE2 inhibits cytokine generation from human lung macrophages. This was determined by using recently developed EP receptor ligands. Experimental Approach: The effects of PGE2 and EP‐selective agonists on LPS‐induced generation of TNF‐α and IL‐6 from macrophages were evaluated. The effects of EP2 ‐selective (PF‐04852946, PF‐04418948) and EP4 ‐selective (L‐161, 982, CJ‐042794) receptor antagonists on PGE2 responses were studied. The expression of EP receptor subtypes by human lung macrophages was determined by RT‐PCR. Key Results: PGE2 inhibited LPS‐induced and Streptococcus pneumoniae ‐induced cytokine generation from human lung macrophages. Analysis of mRNA levels indicated that macrophages expressed EP2 and EP4 receptors. L‐902, 688 (EP4 receptor‐selective agonist) was considerably more potent than butaprost (EP2 receptor‐selective agonist) as an inhibitor of TNF‐α generation from macrophages. EP2 receptor‐selective antagonists had marginal effects on the PGE2 inhibition of TNF‐α generation, whereas EP4 receptor‐selective antagonists caused rightward shifts in the PGE2 concentration–response curves. Conclusions and Implications: These studies demonstrate that the EP4 receptor is the principal receptor that mediates the anti‐inflammatory effects of PGE2 on human lung macrophages. This suggests that EP4 receptor agonists could be effective anti‐inflammatory agents in human lung disease.